Piper delirioi (Piperaceae), a new species from southeastern Brazil - Sarnaglia Junior, Valderes Bento; Guimarães, Elsie Franklin (Phytotaxa, 2015)
Piper delirioi Sarnaglia & E. F. Guim. (Piperaceae), is a new species from southeastern Brazil (Espírito Santo State) proximately related to P. aduncum and P. gaudichaudianum. Although considered a taxonomic novelty, it is already regarded as endangered by the IUCN standards, due to its limited distribution area of about 250 km². We present complete description, taxonomic and geographic notes, and illustrations.